Longitudinal view on Ghana’s parliamentary practices - Boafo-Arthur, K. (African Parliaments: Between Governance and Government, 2005)
This chapter addresses the development of parliamentary practices and hazards what may happen in light of what currently seems as an entrenchment of democratic governance in Ghana. This ambitious scheme cannot by any means claim to offer an exhaustive survey of cumulative events that in reality span a period of over 150 years when the Bond of 1844 that placed the coastal Fante states under British suzerainty was signed. I attempt only to scratch the surface and elucidate the struggle to control Ghana’s legislature from the distant colonial past to the present. © M.A. Mohamed Salih, 2005.